Effects of Crude Oil Contamination on Soil Physical and Chemical Properties in Momoge Wetland of China - Wang, Ying; Feng, Jiang; Lin, Qianxin; Lyu, Xianguo; Wang, Xiaoyu; Wang, Guoping (Chinese geographical science, 2013)
Large oilfields are often coincidentally located in major river deltas and wetlands, and potentially damage the structure, function and ecosystem service values of wetlands during oil exploration. In the present study, the effects of crude oil contamination during oil exploration on soil physical and chemical properties were investigated in marshes of the Momoge National Nature Reserve in Jilin Province, China. The concentrations of total petroleum hydrocarbons in the marsh soil near the oil wells are significantly higher than those in the adjacent control marsh. Soil water contents in oil-contaminated marshes are negatively correlated with soil temperature and are significantly lower than those in the control area, especially in fall. Crude oil contamination significantly increases the soil pH up to 8.0, and reduces available phosphorus concentrations in the soil. The concentrations of total organic carbon are significantly different among sampling sites. Therefore, crude oil contamination could potentially alkalinize marsh soils, adversely affect soil fertility and physical properties, and cause deterioration of the marshes in the Momoge National Nature Reserve. Phyto-remediation by planting Calamagrostis angustifolia has the potential to simultaneously restore and remediate the petroleum hydrocarbon-contaminated wetlands. Crude oil contamination affects the soil physical and chemical properties, so developing an effective restoration program in the Momoge wetland is neccesary.